An Intersectional Understanding of International Female Doctoral Students’ Experiences: A Narrative Inquiry (Comparative & International Education Series, 2022)
International PhD students face multiple challenges in their academic learning experiences, including language barriers, cultural differences, and having to deal with personal matters while negotiating everyday life in a foreign country. Nested within the epistemological positioning of feminist standpoint theory and intersectionality, this chapter explores the multiple layers of socio-cultural and academic study experiences of international female doctoral students in the Australian tertiary education system. Using a narrative inquiry approach, the analysis and discussion draw on students’ personal stories to open up a space to better understand the complexity of international female doctoral students’ experiences when studying in Australia.